Connecting Sectors and Systems for Health Results - Pierre-Louis, Anne Maryse (Policy Notes, 2012)
Strengthening public health, that is, improving the health of whole populations through action across all relevant sectors is at the heart of the World Bank's mission. This policy note takes stock of the global progress in public health over the past decade; lays out the challenges that must be addressed for this progress to be sustained and accelerated; and proposes an approach for the Bank to maximize its contribution to public health in the years ahead. This note comes at a critical juncture, given the important gains made in public health over the past decade. Key global indicators, including life expectancy at birth, under-five mortality and maternal mortality, have shown steady improvement, while initiatives such as the scale-up of polio vaccination and the distribution of bed nets to combat malaria have saved millions of lives. The Bank is proud to have worked with countries and development partners to contribute to these achievements. The note emphasizes that the Bank will need to root its future public health efforts in its areas of comparative advantage, including its capacity to analyze the economic and development impact of health investments, and its extensive experience in working across sectors for health results. The Bank finances investments in all the sectors that impact health, including education, social protection, infrastructure, water and sanitation and transportation, to name a few, and is well placed to help mobilize such sectors through coordinated, population-based interventions to improve health and accelerate development. Given its analytic capability, the Bank has a potentially critical role to play in focusing finite budgets on the most cost-effective actions, particularly in prevention and health promotion